PELATIHAN PRODUKSI ARANG DAN ASAP CAIR CANGKANG KEMIRI DI DESA ALU SULAWESI BARAT - Zulkahfi, Zulkahfi; Ilham, Ilham (LPPM Universitas Nusa Mandiri, 2026)
Renewable energy can be an alternative to fossil fuels, which have a negative impact on the environment. The potential for alternative energy that can be developed from candlenut shells is candlenut shell charcoal, which, along with other products, can produce liquid smoke that can be used as a pesticide and insecticide for agriculture and plantations. Farmers in Kelompok Tani Hutan (KTH) Malilu Sipakainga Alu harvest a lot of candlenuts, but the shells have never been utilized and are even considered waste. This activity is a community service project with the Malilu Sipakainga KTH to convert candlenut shell waste into marketable products. Therefore, the objective of this activity is to improve the skills of Malilu Sipakainga KTH members in producing charcoal and liquid smoke from candlenut shells using pyrolysis technology in the village of Alu, West Sulawesi. In addition, this activity is beneficial for increasing the market value of candlenut commodities and the income of farmer groups. The activity was carried out in several stages, starting from preparation and observation, pyrolysis technology development, socialization, handover and training on pyrolysis technology, to analysis of the success of socialization and training. The results of the activity showed that the socialization activity consisted of two sessions, namely charcoal and liquid smoke from candlenut shells, and the handover of one pyrolysis unit with specifications that have condensation and can accommodate up to 70 kg of candlenut shells. The handover and training on the use of the technology with partners resulted in the production of charcoal and liquid smoke from candlenut shells. The community service activity was carried out successfully, as indicated by the participants' increased understanding of 40%-60% after the activity was implemented.